2013
DOI: 10.19026/rjaset.6.3695
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on A Diesel Engine Fueled with Soybean Biodiesel

Abstract: Biodiesel is a renewable and environmentally friendly alternative fuel derived from natural fats or vegetable oils and it is considered as an attractive alternative to replace diesel fuels. To optimize the application of biodiesel on vehicle diesel engines, the power and fuel economies performances of a diesel fueled with soybean biodiesel were investigated under different engine loads and speeds. Experimental results show that, compared with diesel fuel, with increase in the biodiesel in the blends, the brake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…They observed that the torque initially increased with the addition of biodiesel until it reached a maximum value at B17.5 and then torque decreased with further increase in biodiesel content in fuel blend. Song et al [6] using soybean biodiesel tested on a four cylinder supercharged direct injection engine also observed increase in torque with the increase of biodiesel content in fuel blend. With respect to specific fuel consumption, most researches agree [2,3,5,6] that the fuel consumption of biodiesel blends became higher as biodiesel content in fuel blend was increased.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…They observed that the torque initially increased with the addition of biodiesel until it reached a maximum value at B17.5 and then torque decreased with further increase in biodiesel content in fuel blend. Song et al [6] using soybean biodiesel tested on a four cylinder supercharged direct injection engine also observed increase in torque with the increase of biodiesel content in fuel blend. With respect to specific fuel consumption, most researches agree [2,3,5,6] that the fuel consumption of biodiesel blends became higher as biodiesel content in fuel blend was increased.…”
Section: Introductionmentioning
confidence: 92%
“…Song et al [6] using soybean biodiesel tested on a four cylinder supercharged direct injection engine also observed increase in torque with the increase of biodiesel content in fuel blend. With respect to specific fuel consumption, most researches agree [2,3,5,6] that the fuel consumption of biodiesel blends became higher as biodiesel content in fuel blend was increased. How H.G et al [7] also tested CME using a CRDi diesel engine with varying brake mean effective pressure at a constant speed and observed a similar trend.…”
Section: Introductionmentioning
confidence: 92%